Black cohosh extracts and powders induce micronuclei, a biomarker of genetic damage, in human cells. (18th April 2018) - Smith‐Roe, Stephanie L.; Swartz, Carol D.; Shepard, Kim G.; Bryce, Steven M.; Dertinger, Stephen D.; Waidyanatha, Suramya; Kissling, Grace E.; Auerbach, Scott S.; Witt, Kristine L.
Abstract : Black cohosh extract (BCE) is a widely used dietary supplement marketed to women to alleviate symptoms of gynecological ailments, yet its toxicity has not been well characterized. The National Toxicology Program (NTP) previously reported significant increases in micronucleated erythrocytes in peripheral blood of female Wistar Han rats and B6C3F1/N mice administered 15–1, 000 mg BCE/kg/day by gavage for 90 days. These animals also developed a dose‐dependent nonregenerative macrocytic anemia characterized by clinical changes consistent with megaloblastic anemia. Both micronuclei (MN) and megaloblastic anemia can arise from disruption of the folate metabolism pathway. The NTP used in vitro approaches to investigate whether the NTP's test lot of BCE, BCEs from various suppliers, and root powders from BC and other cohosh species, were genotoxic in general, and to gain insight into the mechanism of action of BCE genotoxicity. Samples were tested in human TK6 lymphoblastoid cells using the In Vitro MicroFlow® MN assay. The NTP BCE and a BC extract reference material (XRM) were tested in the MultiFlow ® DNA Damage assay, which assesses biomarkers of DNA damage, cell division, and cytotoxicity. The NTP BCE and several additional BCEs were tested in bacterial mutagenicity assays. All samples induced MN when cells were grown in physiological levels of folic acid. The NTP BCE and BC XRM produced activity patterns consistent with an aneugenic mode of action. The NTP BCE and five additional BCEs were negative in bacterial mutagenicity tests. These findings show that black cohosh preparations induce chromosomal damage and may pose a safety concern. Environ. Mol. Mutagen. 59:416–426, 2018. © 2018 Published 2018. This article is a US Government work and is in the public domain in the USA.